Energetische Silomaisnutzung in der Biogasproduktion: Eine räumlich-ökonometrische Analyse; The Use of Silage Maize for Biogas Production - A Spatial Econometric Approach - Lukas Scholz; Andreas Meyer-Aurich; Dieter Kirschke (German Journal of Agricultural Economics (GJAE), 2016)
– The expansion of silage maize production has experienced a dynamic development in recent years. This happened against the background of continuously decreasing cattle numbers and a rapid increase in biogas production. Available information on actual cultivated land with silage maize for biogas production in Germany diverges due to different methods of calculation between 500 000 ha and 1 800 000 ha for the year 2010. Based on the spatial econometric models developed in this study, estimates of the use of silage maize in biogas production and dairy and cattle farming are given for the state of Bavaria. The average estimated share of silage maize of agricultural land in Bavaria is 4.5 % for biogas production and 7.2 % for dairy and cattle farming. About 40 % of total production of silage maize is used for energy purposes on average. Further, the results of the study allow for a spatially differentiated view on the use of silage maize for biogas production.
Keywords: 330